A Respiratory Symptoms as Sequelae of Fever- An Ayurvedic Insight - Devi D Das; Arjun Chand C P; Arun Pratap; Kasthuri Nair A (AYUSHDHARA, 2025)
Respiratory symptoms are one of the most prevalent clinical presentations in the current scenario. These symptoms often emerge following viral or bacterial infections, typically accompanied by fever. Certain antimicrobial therapy only destroys the pathological factors, but the impact created by the organism persists in the body, later manifesting as sequelae in different systems. In the respiratory system, it is exhibited in the form of cough, dyspnoea, and wheezing. The Ayurvedic classical text also documents similar observations in the context of Jvara Upadrava, highlighting respiratory issues such as Swasa, Kasa, and Hikka. This is an approach to narrate the modified pathophysiology of respiratory symptoms that occur as sequelae of fever through Ayurvedic insight.